Multicellular Tumor Spheroids: A Comprehensive Review of Tumor Biology and Drug Delivery Strategies - Rahman, Aziz Ur; Maqsood Ur Rehman; Islam , Zahoor; Mehwish; Muhammad Zain Ul Abideen; Rashid, Sana (Indus Journal of Bioscience Research, 2025)
Background: Multicellular tumor spheroids (MCTS) have emerged as pivotal three-dimensional (3D) in vitro models for replicating the tumor microenvironment. They offer significant advantages over two-dimensional (2D) cultures, particularly for studying drug resistance, hypoxia, and delivery mechanisms. Objective: To systematically evaluate the application of MCTS in cancer research, emphasizing their role in drug delivery, resistance mechanisms, and tumor modeling, with a detailed subgroup and cumulative analysis of their efficacy. Methods: A comprehensive review was performed using PubMed, Scopus, and Web of Science databases, focusing on studies published between 2000 and 2023. Keywords such as “multicellular tumor spheroids,” “3D cell culture,” and “drug resistance” were used. Subgroup analyses were conducted on studies focusing on hypoxia, biomaterial-based MCTS, and high-throughput systems. Numerical data were synthesized for cumulative insights, comparing MCTS against traditional 2D models. Results: MCTS increased drug penetration by 32% (95% CI: 28–36%, p < 0.001) compared to 2D cultures. Subgroup analysis revealed a 40% (p < 0.01) rise in drug resistance under hypoxic conditions. Biomaterial-based MCTS improved extracellular matrix heterogeneity by 58% (p < 0.05). High-throughput systems reduced spheroid size variability by 43%, enhancing reproducibility. Conclusion: MCTS significantly improve tumor mimicry and drug evaluation precision compared to 2D models. Their scalability and vascularization remain key areas for advancement, with subgroup analyses highlighting their potential for personalized medicine.